2016
DOI: 10.1016/j.electacta.2016.05.182
|View full text |Cite
|
Sign up to set email alerts
|

Amine-appended polyaniline as a water dispersible electroactive polyelectrolyte and its integration into functional self-assembled multilayers

Abstract: We present an effective and simple method for the synthesis of poly(3-aminobenzylamine) (PABA) using a chemical oxidation strategy in aqueous solution. The polymer was characterized by NMR, LDI-TOF mass spectrometry, UV-visible, XPS and ATR-FTIR spectroscopies. Stable acidic dispersions were employed for the construction of layer-by-layer assembled films with polyanions, which effectively act as dopants of the electroactive component as revealed by spectroscopic analysis. The assembled films were electroactive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 90 publications
1
17
0
Order By: Relevance
“…The methylene proton signal appeared at 3.34 ppm (a) and the aromatic protons attached to the benzenoid and quinoid rings of PABA showed the multiplet signals 6.55–7.31 ppm (b–i). It could be concluded that the synthesis of PABA from the ABA monomer using APS as an oxidant was successful in this study [ 36 , 45 ].…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…The methylene proton signal appeared at 3.34 ppm (a) and the aromatic protons attached to the benzenoid and quinoid rings of PABA showed the multiplet signals 6.55–7.31 ppm (b–i). It could be concluded that the synthesis of PABA from the ABA monomer using APS as an oxidant was successful in this study [ 36 , 45 ].…”
Section: Resultsmentioning
confidence: 89%
“…The peak at 240 nm was assigned to the π–π* transition within the aniline moiety, whereas the peak at 300 nm was assigned to the π–π* transition attributed to benzenoid rings and lone pair electrons of nitrogen [ 40 , 46 ]. In addition, the PABA exhibited a broad absorption band around 500 nm, which was attributed to the excitonic π–π* transition from the highest occupied molecular orbital (HOMO) of the valence band to the lowest unoccupied molecular orbital (LUMO) of the conduction band [ 36 , 40 , 47 ]. For PL measurement, the ABA monomer and PABA solutions were excited in the range of 340–380 nm ( Figure S3 of Supplementary Information ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This correlation indicates that the electroactive component integrated in the LbL assembly is electrochemically connected within the films, which is not necessarily valid for all the LbL assemblies with non-electroactive counterparts. 55 Thus, it is possible the functional integration of the electroactive block in the composite films by this simple nanoarchitectonic approach. nanocrystals, cyclic voltammetry in air-saturated solutions after different functionalization steps was performed between 0.5 and -0.6V (Fig.…”
Section: Electrochemical Behavior Of the Lbl Assembliesmentioning
confidence: 99%
“…Additionally, PABA also displays enhanced electroactivity in neutral solutions compared with PANI. 23,24 Owing to its improved processability in aqueous solution, PABA seems to be a better candidate than PANI for the preparation of electrostatically-driven complexes with surfactants. On the other hand, the particular interaction between protonated amines and phosphate anions has been extensively recognized.…”
mentioning
confidence: 99%